The Role of Gen Z Students as Agents of Change in Digital Economic Development Policy Innovation - Wida Aristanti; Wahyu Lestari; Windy Permata Suyono (Benefit: Journal of Bussiness, Economics, and Finance, 2025)
Generation Z, born and raised in the digital era, possesses unique characteristics as digital natives, positioning them as potential actors in driving innovation in economic development policy in Indonesia. Gen Z, particularly university students, play roles not only as technology users but also as creators of sustainable development solutions. This study aims to examine the role of Gen Z students as agents of change in the formulation and implementation of economic policies, especially in the digital economy sector. Using a qualitative approach and case study method, the research found that Gen Z students demonstrate high levels of participation in various activities such as digital-based entrepreneurship, public policy advocacy, and the use of social media and information technology to strengthen the economic ecosystem. They are also active in creative and collaborative communities that foster crosssector innovation. These findings highlight the importance of involving young generations in public policy processes and the need for institutional support, such as business incubators, entrepreneurship training, and access to funding. The strategic implication of this study is the necessity for governments and stakeholders to design inclusive, adaptive, and responsive policies that align with the dynamics and aspirations of today’s generation in order to enhance their contribution to national creative economic development.